Psychometric propertis: ADHD rating scale IV self-report - Ramos-Galarza, Carlos (2016)
Introduction: The ADHD Rating Scale IV (ADHD RS IV) is a questionnaire with 18 items which evaluates attention deficit, hyperactivity and impulsivity that make up the attention deficit hyperactivity disorder (ADHD). The contribution of this study to the research of ADHD are two: the analysis of the psychometric properties of ADHD RS IV in an adaptation of self-report format and reporting a study in a context where there is not a previous research. Method: The research is based on a quantitative no experimental design, transactional court, in order to adapt an instrument in a new context. Data analysis was based on statistical processes Cronbach's alpha, correlation of each item with the total scale, measures of central tendency and dispersion, comparison of means using Student's t, Pearson correlation and confirmatory factor analysis. Results: We found adequate internal consistency coefficients for scales attention deficit, hyperactivity/impulsivity and total ADHD. Each of the scales were significantly correlated and they permit evaluate different aspects of human cognition and behavior. The goodness of fit of the model tested in confirmatory factor analysis allows us to replicate the scale in its classic composition. Conclusions: The ADHD RS IV has adequate psychometric properties to be administered in the form of self-reporting for the assessment of impulsivity/hyperactivity, attention deficit or a combination of both symptomatology in the Ecuadorian context. © 2016, Sociedad de Neurologia Psiquiatria y Neurocirugia. All rights reserved.